Evaluación del uso de la cáscara de cacao como sustituto parcial de la matriz polimérica en la obtención de espumas de poliuretano (2019)
In the research, the effect of the inclusion of cocoa pod husk in the formulation of rigid polyurethane foams was evaluated, based on the percentage replacement of the hydroxyl groups given to the system due to the use of the commercial polyol, by the hydroxyl groups present in the lignocellulosic biomass. The material used was the dried and ground cocoa pod husk of the trinitarian species, with particle size between 88μm and 150μm, which was included in the polymer matrix according to the percentages of incorporation of 5%, 10%, 15% and 20%. In order to demonstrate the change in the material due to the inclusion of the cocoa husk, physical and mechanical properties such as density, water absorption and compressive strength were evaluated. An improvement was obtained in each of the properties, this follows a behavior directly proportional to the increase in the percentage of replacement of hydroxyl groups of the commercial polyol, by biopolyol. It was established that the rigid polyurethane foam that has better properties is that of a replacement percentage of 20%, for that foam, the density increased from 24.03 kg/m3 referred to the standard sample, up to 27.90 kg/m3, similarly, the percentage of water absorption increased from 49.89% in the target, to the value of 60.15% and finally, the compressive strength measured in parallel direction to the growth of the foam, showed an increase up to the value of 0,15 MPa, starting from a standard value of 0,11 MPa.